ANALISIS PROSPEKTIF UNTUK KEBERLANJUTAN PENGELOLAAN TPS 3R DI KOTA PANGKALPINANG A PROSPECTIVE ANALYSIS FOR TPS 3R SUSTAINABILITY IN PANGKALPINANG CITY - Meri Nopriani; Akhmad Fauzi; Nuva Nuva (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The implementation of the TPS 3R program is one strategy for overcoming the waste problem in Pangkalpinang City. To ensure the sustainability of the program thus this study is carried out by analyzing the factors and actors that influence its implementation. This study uses the MICMAC method to identify key variables, and the MACTOR method to identify the influence and role of actors. The results show that the role of regulation and community participation is very strong in influencing all variables in the system, so it must be the focus which should be a concern bypolicymakers. The most important actors in supporting the success of the program are DLH, KSM, DPUPR, PLN and Pertamina. A strong alliance of these actors is needed to support the success and sustainability of the program.